2019
DOI: 10.1007/s11356-019-05122-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk assessment of antibiotics in agroecosystems: ecotoxicological effects on aquatic microbial communities and dissemination of antimicrobial resistances and antibiotic biodegradation potential along the soil-water continuum

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 92 publications
(76 reference statements)
0
18
0
Order By: Relevance
“…The potential of fungal members of the microbial community to degrade SUL in soils was documented by their enhanced activity (Chen et al, 2016) or increased proportion of fungal biomass in loamy sand soil (Gutiérrez et al, 2010) or in Chernozem Haplic and Phaeozem Greyic (Frková et al, 2020). Antibiotics are efficiently degraded by various soil microorganisms (Wang and Wang, 2018;Martin-Laurent et al, 2019), including resistant soil bacteria, which exhibit increased numbers due to environmental pollution (e.g., Fahrenfeld et al, 2014;Goodman and Gilman, 2011;Heuer et al, 2008). In our study, the second model for SUL includes K F and biomass of Gram-negative bacteria (Table 5) likely because these bacteria are more likely to acquire and spread plasmid-mediated antibiotic resistance in the environment (Stokes and Gillings, 2011).…”
Section: Estimation Of Dissipation Half-lives From K F Values Soil Pmentioning
confidence: 99%
“…The potential of fungal members of the microbial community to degrade SUL in soils was documented by their enhanced activity (Chen et al, 2016) or increased proportion of fungal biomass in loamy sand soil (Gutiérrez et al, 2010) or in Chernozem Haplic and Phaeozem Greyic (Frková et al, 2020). Antibiotics are efficiently degraded by various soil microorganisms (Wang and Wang, 2018;Martin-Laurent et al, 2019), including resistant soil bacteria, which exhibit increased numbers due to environmental pollution (e.g., Fahrenfeld et al, 2014;Goodman and Gilman, 2011;Heuer et al, 2008). In our study, the second model for SUL includes K F and biomass of Gram-negative bacteria (Table 5) likely because these bacteria are more likely to acquire and spread plasmid-mediated antibiotic resistance in the environment (Stokes and Gillings, 2011).…”
Section: Estimation Of Dissipation Half-lives From K F Values Soil Pmentioning
confidence: 99%
“…A major concern regarding the general contamination of freshwaters (and other environmental compartments) by sulfonamides (and other antibiotics) is the increasing occurrence of microbial antibiotic resistance in the environment (Martin-Laurent et al, 2019). At sub-lethal doses, antibiotics exert a selection pressure that will promote the emergence and development of antibiotic resistance (for a complete review on antibiotic resistance mechanisms, see McDermott et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that once the antibiotics reach the aquatic environment, due to their slow biodegradation, some of these drugs may persist in the environment for longer time due to bioaccumulation and biomagnification. Antibiotics in the natural environment, even in low quantities, can affect the survival, reproduction, and metabolism of aquatic organisms, as well as alter the structure of communities and ecosystem functions (Pereira et al 2015;Martin-Laurent et al 2019).…”
Section: Discussionmentioning
confidence: 99%